Effects of water extract of propolis on fresh shibuta (Barbus grypus) fillets during chilled storage - Duman, Muhsine; Ozpolat, Emine (Elsevier Sci Ltd, 2015)
The present study examined the effects of water extract of propolis on the chemical, microbiological and sensory quality in vacuum-packed fresh shibuta (Barbus grypus) fillets during storage at 2 degrees C. Treatments in the study included the following: control (PO) without extract of propolis, 0.1 (P1), 0.3 (P3) and 0.5 (P5) % (v/w) the water extract of propolis, respectively. After 24 days of storage, the total volatile basic nitrogen (TVB-N) values were 57.76, 44.66, 42.23 and 36.5 mg/100 g, and total viable counts (TVC) were 8.9, 8.3, 7.96 and 6.95 log cfu/g, for water extract of propolis additions of 0.1 (P1), 0.3 (P3), 0.5 (P5) and 0 (control; PO) % (v/w), respectively. The highest acceptable TVB-N value was adopted as 30 mg/100 g, corresponding to shelf lives of 9, 15, 18 and 21 days for PO, P1, P3 and P5, respectively. Addition of 0.1% water extract of propolis extended the product's shelf-life by approximately 6 days, whereas the 0.5% water extract of propolis resulted in a significant shelf-life extension of the shibuta fillets, i.e. by approximately 12 days, according to sensory data, as compared to the control sample. (C) 2014 Elsevier Ltd. All rights reserved.
2nd Food Integrity and Traceability Conference -- APR 08-10, 2014 -- Queen's Univ, Belfast, NORTH IRELAND
Keywords: Shibuta; Water extract of propolis; Quality parameters; Shelf-life